A Study on Rural Marketing in India - KAVITHA , S.; RAMAJAYAM, V. (International Journal of Psychosocial Rehabilitation, 2020)
Rural marketing is two sided process which occupies both inflow of products into rural areas from urban areas and outflow of manufactured goods from rural to urban area. The Indian rural market has mammoth potential which unlocks many money-making avenues for companies but impend the rural markets is not as much as easy as it seems. Companies face many problems and challenges. They will have to take unsympathetic attempts to discover rural markets profitably. This paper discloses the thought of rural marketing in India, potentialities of rural markets and confronts among rural marketers. Major segment of rural markets is still untapped. The Indian rural market these days not only limited to customers and agricultural products marketing. Agricultural marketing only engage the movement of agricultural products from place of farmer to place of purchase. But, the rural marketing has gone far away from these. The present situation signifies that the future of rural markets is very hopeful and its size will definitely increase manifold in coming years.